Liane Tooth interviewed by Nikki Henningham for the Sport oral history project - Tooth, Liane, 1962-; Henningham, Nicola, 1960- (2008)
Liane Tooth, an inaugural inductee into the Australian Hockey Hall of Fame (July, 2008) discusses the importance of individual accolades to a player of a team sport and peer recognition; the success of the Hockeyroos; her career in sport; her family background; her introduction to hockey; her school and university preferences and achievements, graduating B.Ed (Phys Ed) from University (1983); playing sport during tertiary study; international travel with sport; her progression through the sport from club player to member of the Hockeyroos; the Australian Institute of Sport (AIS), Hockey unit in Perth; playing surfaces and development of hockey sticks through the years; her strengths as a player; sporting injuries; being selected to go to the 1984 Olympic Games; participation in the Olympic Games opening ceremony; origins of the name Hockeyroo; lead up to 1988, Seoul Olympics and their gold medal win; the importance of AIS programs; impact of developments in sports science and sports psychology; World Cup in Sydney (1990); Barcelona Olympic games (1992); Sydney 2000; Ric Charlesworth; new rules enabled a new game plan; training regimes.
Tooth discusses the Atlanta Olympic Games (1996) and their win; international rivalries and friendships; employment while playing; development of career after playing career was finished; working in the area of women's and girls sports development; Womensport West; moving into talent development and high performance; barriers to women's continued participation in sport; her current role in talent development; working with Western Australian Institute of Sport (WAIS) to identify talent in certain targeted sports; her current job; her attitude and relationship with officials and umpires; her experience of umpiring; her involvement in the Olympic Movement after her own Olympic career; the Olympic Athletes Commission's role; development of 'ASPIRE' team values; the commercial nature of Olympics; her attitude to the problem of drugs in sport; Beijing Olympics (2008); the people who supported her throughout her sporting career; life lessons learned through involvement in sport; importance of team mates and friendships.
Recorded on 23 July, 2008 in Perth, W.A.
Mode of access: Online.
Liane Tooth competed in four Olympic games as a member of the Hockeyroos. Winning a gold medal in the Seoul (1988) and Atlanta Olympic Games (1996). She has won numerous awards including a Medal of the Order of Australia (OAM), 1989 and her induction into the Australian Hockey Hall of Fame (July, 2008).
Timed summary (7 p.) and uncorrected transcript (typescript, 89 leaves)
Keywords: Tooth, Liane, -- 1962- -- Interviews; Hockeyroos (Team); Field hockey players -- Australia -- Interviews; Athletes -- Australia -- Interviews; Field hockey; Olympics; Olympics -- Participation, Australian